ANALISIS SEMIOTIKA NILAI-NILAI SOSIAL TEORI SEMIOTIKA FERDINAND DE SAUSSURE PADA NOVEL “HUJAN” KARYA TERE LIYE - Sujiono; Anggita, Della (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research aims to analyze the social values ​​contained in the novel Rain by Tere Liye using Ferdinand de Saussure's semiotic analysis model. This research uses descriptive qualitative methods. Research data was obtained from the 14th printing of Tere Liye's novel Rain and published in August 2023. The data collection technique was carried out using reading and note-taking techniques. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The research results show that in the novel Rain there are social values ​​such as the values ​​of helping, caring, kinship, empathy, justice and democracy which are represented through verbal and nonverbal signs. These social values ​​are expressed explicitly through the characters' conversations and monologues, and implicitly through the characters' actions and attitudes in living their lives. Thus, it can be concluded that through the medium of novels, authors are able to convey social values ​​that can provide positive examples for readers.